Kualitas Pelayanan Pramusaji Terhadap Kepuasan Tamu di Restoran Cashmere Aston Solo Hotel - Shinta Mega Pertiwi; Sunyoto Suyanto; Denny Asmara (Jurnal Pariwisata Indonesia, 2020)
This research aimed to know the quality of waiter service toward gues satisfaction in cashmere Aston solo hotel restaurant. The type of this research was qualitative method with distributing questionnaires to 10 guest satisfaction in cashmere Aston Solo Hotel restaurant and data collection techniques obtained from observation, questionnaires, interview, documentation, literature review by comparing between the theory That had been done by the researcher. The service quality was very important for guest satisfaction because the key of satisfaction can be seen by the guests' wishes according to the expectation. In this result of research obtained from the results of the questionnaire calculation seen by service quality with speed indicator equal to 78%, 60% accuracy, 97% friendliness, 98% service comfort. Meanwhile, from guest satisfaction with the indicator of conformity with expectations of 98%, interest in revisiting is 94%, willingness to recommend is 100%. So that the quality of service is the main number and very important, because it includes speed, accuracy, friendliness, the convenience of the services provided will greatly help in improving the work operations of the waiter, so that from there the waiter can improve the quality of service in serving guests at the restaurant. Then it will create guests who get satisfaction with the service and also guests will come back again to enjoy the services and food and drinks at the restaurant so that they are able to increase revenue at the restaurant. The existence of success in a restaurant is seen from the quality of waiter service as well as the quality of food and beverages available in the restaurant.